2013
DOI: 10.1111/aogs.12094
|View full text |Cite
|
Sign up to set email alerts
|

Changes in exhaled breath condensate pH in healthy and asthmatic pregnant women

Abstract: EBC pH is higher in healthy pregnant women but not in asthmatic pregnant women compared with data from healthy non-pregnant women, indicating that oxidative inflammatory processes induced by asthma may compromise the regulatory mechanisms causing alkaline pH in the airways during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although some studies showed modification in global metabolism during pregnancy [ 37 ], few studies focused on the EBC of these subjects. Some authors highlighted a higher EBC pH in healthy pregnant women than that from healthy non-pregnant women [ 38 ]. These findings may have an impact on metabolic profile and need to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies showed modification in global metabolism during pregnancy [ 37 ], few studies focused on the EBC of these subjects. Some authors highlighted a higher EBC pH in healthy pregnant women than that from healthy non-pregnant women [ 38 ]. These findings may have an impact on metabolic profile and need to be fully explored.…”
Section: Discussionmentioning
confidence: 99%
“…Wood et al showed the influence of Mycoplasma pneumonia infection in asthmatic children on EBC pH [ 54 ], but their follow-up study did not confirm the primary thesis [ 55 ]. Pregnancy did not alter the acidity of airways in asthmatic women [ 56 ]. Active smoking, which is connected with worse asthma management, lowered pH in samples [ 57 , 58 ].…”
Section: Biomarkers In Exhaled Breath Condensate Of Asthmatic Patientsmentioning
confidence: 99%
“…albuterol/salbutamol usage; methacholine induction of airway obstruction; and hypoventilation and hyperventilation [10,16,18]. Although gender does not influence EBC pH, it is noteworthy that pregnant women have higher pH values than non-pregnant individuals [19]. In addition, obesity does not influence EBC pH unless it is connected with obstructive sleep apnea [20], [21].…”
Section: Physiological Ph Of Ebcmentioning
confidence: 99%
“…Consequently, it is very difficult to form strong comparisons of the pH values between the control groups in the various studies. or FVC in adult [19,27,29] or pediatric population [26,30,32]. The acidity of the sample is normalized when the patient's exacerbation period is properly treated [42].…”
Section: Physiological Ph Of Ebcmentioning
confidence: 99%